Atypical Proliferating Trichilemmal Cyst with Malignant Breast Skin Transformation: A Case Report and Review of the Literature - Marino Antonio Capurso-García; Verónica Bautista-Piña; Alan Pomerantz; Javier Andrés Galnares-Olalde; Ruben Blachman-Braun; Sergio Rodríguez-Rodríguez; Monica Goldberg-Murow (Case Reports in Oncological Medicine)
Proliferating trichilemmal tumors (PTTs) are benign adnexal skin neoplasms that arise from the outer root sheath of the hair follicle. These tumors are most commonly observed on the scalp and occur, most of the time, in elderly women. Malignant transformation of these neoplasms is a rare event; less than 50 cases have been reported in the English medical literature. We present the case of a 39-year-old Hispanic woman with a tumor located on the skin of one of her breasts that in her third surgical procedure the histologic examination revealed the presence of a malignant proliferating trichilemmal tumor (MPTT). Furthermore, a review of the medical literature and a discussion of the clinical and pathologic features of this rare entity are provided.